Madurese Local Wisdom Values in the Performing Arts of Masks and Loddrok - Alif Akbar, Syekhfani; Alif Ramdlani, Mohammad; Qadar Basri, Syaiful (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
Cultural preservation is a critical endeavor, especially in a culturally diverse nation like Indonesia. Madurese culture, known for its uniqueness, has been extensively studied, yet ongoing efforts are required to safeguard its local traditions and values. Literature serves as a vital medium for preserving culture, acting as a bridge to transmit and sustain cultural identity. One notable literary work, Lebur, exemplifies this by exploring traditional Madurese values. This study aims to promote cultural preservation through arts performances rooted in local Madurese traditions. Employing the Sociology of Literature as the theoretical framework, the research utilizes a descriptive-qualitative methodology. Data sources include field surveys and literature studies, which are subsequently analyzed through sociological perspectives on literature. The findings underscore the pivotal role of arts performance in preserving and promoting Madurese traditional values. By drawing on the rich heritage embedded in local traditions, such performances not only safeguard cultural identity but also enhance societal appreciation for these values. The analysis highlights the sociological significance of integrating traditional values into arts performances as a means of fostering cultural continuity and community engagement. This research contributes to the discourse on cultural preservation, demonstrating how literature and performance art can serve as effective tools for sustaining local traditions. It offers valuable insights for cultural practitioners, educators, and policymakers aiming to develop strategies for preserving Indonesia's diverse cultural heritage.